Effective Enteral Treatment of Antibiotic for Patient with Respiratory Failure and Septic Shock in the Intensive Care Unit - Maya sari; Wiwi Jaya; Arie Zainul Fatoni (Journal of Anaesthesia and Pain, 2021)
Background: Pneumonia is a lung infection involving pulmonary alveoli caused by microbes, including bacteria, viruses, and fungi. It is a major infection that causes hospitalization and death worldwide and exacts an enormous cost in economic and human terms. The study to assess clinical outcomes for a critically ill patient treated with an enteral antibiotic for bacterial pneumonia is still limited.Case: We reported a case of pneumonia from 68 years old patient that caused respiratory failure and septic shock in the intensive care unit treated by enteral antibiotic and had a good outcome.Conclusion: Pneumonia can cause respiratory failure and septic conditions. Optimum antibiotic management is one of the methods to solve this problem. The benefit of utilizing enteral antibiotics is substantial and probably appropriate in certain patients.